Trends in transport injuries burden and risk factors among children under 14 years old in China: 1990-2019 - Yueliang Chen; Feng Wu; Kele Ding; Zhengfeei Ma; Liping Li (BMC, 2024)
Abstract Background Transport injuries (TI) remains one of leading causes of death in children in China. This study aimed to analyze the temporal trend of disease burden and associated risk factors of TI among children aged 0-14 years in China, utilizing data from 1990 to 2019. Methods We retrieved data of disease burden and risk factors of TI among children aged 0-14 year in China from 1990 to 2019 from the Global Burden of Disease (GBD) dataset. We estimated incidence rate, death rate, and disability adjusted life years (DALYs) rate with a 95% uncertainty interval (95% UI), stratified by age, sex, and all type-road users. Trends in disease burden with annual percentage changes (APC) and average annual percent change (AAPC) were performed by Joinpoint regression model. Results The incidence rate (AAPC = 1.18%, P < 0.001) of TI among children aged 0-14 years showed an increasing trend, whereas mortality rate (AAPC = -3.87%, P < 0.001) and DALYs rate (AAPC = -3.83%, P < 0.001) decreased annually. Notably, boys experienced a higher increase in incidence (1.30%) compared to girls (1.06%), but a faster decrease in mortality and DALYs rate (-3.90% vs. -3.82%, -3.88% vs. -3.79%, respectively) (P all  < 0.001). Declines in death rates and DALYs rates were observed across all age groups (P all  < 0.001), while remained the highest among children aged 0-4 in 2019. Among different road-type users, cyclist road injuries were identified as the primary cause of TI (182.3 cases per 100,000) while pedestrians were the group with the highest mortality (2.9 cases per 100,000) and DALYs rate (243 cases per 100,000) in 2019. Besides, alcohol use was a significant risk factors for TI, while low temperature appeared to be a protective factor. Conclusion Future efforts must prioritize raising awareness among children and their guardians to mitigate the disease burden of TI in children. It's critical to enhance preventive interventions for boys, children aged 0-4 and vulnerable road users such as pedestrians and cyclists in future.